Kriteria Dan Faktor Risiko Pada Sindroma Metabolik Pada Baseline Vs Follow up 6 Tahun: Studi Kohor Faktor Risiko PTM 2018 - Ratih Oemiati (STIKes Persada Husada Indonesia, 2019)
Epidemiology data indicates the metabolic syndrome prevalence at 20-25% in the world. The metabolic syndrome prevalence of adult population in Europe at present reported at 15%, 14.2% in South Korea and 24 % in America. While in Indonesia 23,34% of the total population experienced metabolic syndrome, 26,2 % in the men and 21,4% in the women. The study aimed at comparing the metabolic syndrome result during baseline and metabolic syndrome 6 years follow up. The samples were taken from 2011 and 2012 screening respondents data source during baseline (N=4665), 6 years observation had been carried out and a complete 2018 evaluation assessment can be analysed to be N=2229. Analysed variables were sociodemografic data, metabolic syndrome indicator and risk factors. Analysis used frequency percentage. Study result showed metabolic syndrome 2018 incident of 151 persons or 19,2 per 1000 person years. A decrease of about 10% occurred in the younger age group and an increase of 3% in the elderly group > 55 years. There was not much changes in the economic status between baseline and 6 years follow-up. An increase in the category of obesity in BMI and central obesity in the abdominal circumference occurred during the 6 years follow-up respectively 13% and 26,6%. Triglyceride result increased almost double and total cholesterol increased 20% compared to baseline period. Diabetes Melitus’s history in metabolic syndrome respondents up twice compared from baseline. There was an adequate category increase in physical activity between the start and at 6th year. However based on Brinkman index, heavy smokers experienced almost 3 times increase compared to baseline period.